PENGARUH COMPANY SIZE, RETURN ON ASSET, NET PROFIT MARGIN, TOTAL DEBT TO TOTAL ASSET DAN DEBT TO EQUITY RATIO TERHADAP INCOME SMOOTHING - Sugiarto, Wiwit (Universitas Slamet Riyadi, 2015)
The purpose of this research is to analyze the significance of the influence of the size of the company, return on assets, net profit margin, total debt to total assets and debt to equity ratio partially or simultaneously against income smoothing on corporate real estate and property in the Indonesia stock exchange. Analyze the dominant variables that affect income smoothing on corporate real estate and property in the Indonesia stock exchange. This research uses a correlation study approach. The population in this research is all real estate companies and property were listed on the Indonesia stock exchange for the period 2011-2013, amounting to as much as 41 companies. The sample in this study as many as 30 companies, sampling techniques using a purposive sampling. Technique of data analysis in this study using logistic regression analysis. The research results obtained conclusions: Variable size enterprise size companies, return on assets, net profit margin, total debt to total assets and debt to equity ratio partially or simultaneously do not affect significantly to income smoothing. The results of the analysis showed that the return on asset was the dominant variables that affect income smoothing on corporate real estate and property. Keywords: company size, return on assets, net profit margin, total debt to total assets, debt to equity ratio and income smoothing